Обґрунтування рецептурного складу хліба пшеничного з додаванням напівфабрикату «маса для формування» - ‪Товма, Лідія Федорівна; Євлаш, Вікторія Владленівна; Коновалова, О. В. (My University, 2019)
З метою розробки рецептурного складу хліба пшеничного «Селянський» як предмет досліджень використовували зразки випеченого хліба пшеничного з масовою часткою напівфабрикату «Маса для формування» 2,5 та 5,0% до маси борошна, який вводили в сухому вигляді при замішуванні тіста. Для визначення органолептичних (за 5-бальною шкалою з урахуванням коефіцієнтів вагомості кожного показника), фізико-хімічних (титрованої кислотності, масової частки вологи, питомого об ’єму, пористості), мікробіологічних (мікробне забруднення: кількість мезофільних аеробних і факультативно анаеробних мікроорганізмів (КМАФАМ, КУО / г); наявність бактерій групи кишкових паличок (БГКП (коліформи), в 0,001 г); виявлення золотистого стафілококу, протея та інших патогенних мікроорганізмів (патогенні мікроорганізми, у т. ч. бактерії роду Salmonella, в 25 г) тощо), структурно-механічних (еластичність, %; модуль еластичності Е, Па; усадка, %,) показників було використано загальноприйняті та стандартні методики. For the purpose of development of the compounding composition of wheat bread “Selianskyi” the samples of baked wheat bread with a mass fraction of semi-finished product “Mass for forming” of 2.5 and 5.0% by weight of flour were used, which was brought into the dry form when kneading the dough. To determine the organoleptic (5-point scale, taking into account the coefficients of weight of each indicator), physicochemical (titrated acidity, mass fraction of moisture, specific volume, porosity), microbiological (microbial contamination: the number of mesophilic aerobic and optional anaerobic microorganisms (grams); the presence of bacteria of the group of “Escherichia coli”; detection of Staphylococcus aureus, Proteus and other pathogenic microorganisms (pathogens, including bacteria of the genus Salmonella, in 25 g; structuralmechanical (elasticity, %; modulus of elasticity E, PA; shrinkage,%,) indicators conventional and standard methods were used. It was established that the introduction of the semifinished product “Mass for forming” in prototypes of wheat bread in the amount of 2.5 and 5.0% by weight of flour compared to the control sample improves its organoleptic properties: taste, color, porosity and crumb condition, except of the sample with the addition of 5.0%, which does not improve the porosity of the crumb. Other indicators were improved. Bread samples with a mass fraction of additives of 2.5%, were characterized by. the highest rates, which were kept for 12 days. Molding also reduces the titrated acidity of wheat bread samples by 0.5oT and the crumb moisture by 2%, increases the specific volume by 1.12% and the crumb porosity by 8% compared to the control sample. The decrease in contamination in experimental samples of bread from wheat by microorganisms for molds was by 4.0—4.5 times, and for yeast — by 2.0—3.0 times.
Keywords: якість; властивості; хліб із борошна пшеничного; рецептура; напівфабрикат «Маса для формування»; quality; recipe; bread made from wheat flour; semi-finished product “Mass for molding”; properties